Towards a methodology for comparing the effectiveness of different alpine ski waxes - Coupe, R. C.; Spells, S. J. (Sports Engineering, 2009)
The aim of this work is to develop a methodology for the glide testing of waxed skis at an indoor ski centre, using artificial snow. Two skiers, one acting as a control with unwaxed skis, undertook the test runs over a 50-m course. Timing gates allowed split times to be measured for a selection of waxes, as well as unwaxed skis. Five runs were conducted for each ski preparation, interlaced with control runs. Unwaxed skis produced similar run times to waxed skis for the complete course, with measurements showing their probable superiority over the first 10 m. A tentative interpretation involves the delay in forming a lubricating meltwater film under waxed skis by comparison with unwaxed skis. Recommendations are made for future measurements, including a longer course, close matching of skiers` masses and ski sizes, all timing systems accurate to 0.001 s, a start 3 m above the first timing gate and more effective methods of wax removal.